Moscatilin suppresses the inflammation from macrophages and T cells - Zhang Ying; Xu Yugang; Jing Xiujie; Lu Wenkui; Zhang Fusen; Qin Chengkun (Open Medicine, 2022)
In this study, we aim to investigate moscatilin in alleviating symptoms of autoimmune liver disease (ALD) in a concanavalin A (ConA)-induced liver injury mouse model and elucidate the underlying mechanisms. ALD mouse models were constructed by intravenous injection of ConA (20 mg/kg) and the serum level of alanine aminotransferase (ALT) was measured using an enzyme-linked immunosorbent assay. Moscatilin in various doses was administered for two days starting from a day before the ConA injection. We showed that moscatilin dose-dependently decreased ALT levels in liver tissue of ALD mouse models. Ifng and Tnfa also showed significant downregulation in liver tissues. Macrophages only showed significant Tnfa downregulation and CD4+ T cells only showed significant Ifng downregulation at high moscatilin doses. In vivo administration of moscatilin induced interleukin-37 upregulation in hepatic tissues. In vitro, moscatilin also induced IL-37 upregulation in hepatic stellate cell line JS-1 rather than immune cells represented by RAW264.7 and CTLL-2 cell lines, suggesting that the hepatic stellate cell is majorly responsive to moscatilin treatment in terms of interleukin (IL)-37 upregulation. Our data indicate that moscatilin could alleviate liver injury in ConA-induced ALD mouse models through anti-inflammatory activities, warranting further development of moscatilin as a new drug in treating ALD.